Estimation of the mean of functional time series and a two‐sample problem. (21st June 2012) - Horváth, Lajos; Kokoszka, Piotr; Reeder, Ron
<x xml:space="preserve">Abstract</x> Summary. The paper is concerned with inference based on the mean function of a functional time series. We develop a normal approximation for the functional sample mean and then focus on the estimation of the asymptotic variance kernel. Using these results, we develop and asymptotically justify testing procedures for the equality of means in two functional samples exhibiting temporal dependence. Evaluated by means of a simulation study and application to a real data set, these two‐sample procedures enjoy good size and power in finite samples.